UTHM Herbs Garden Application Using Augmented Reality - Senan, Norhalina; Md Najib, Nurhakimah Azwani (Applied Information Technology And Computer Science, 2020)
This application is develop to help guide the community in UTHM to recognize the herbs species. Nowadays, the existing method of conveying information about the herbs is by conventional method through a tagging card which is located nearby the herbs. This method is effective but there are no interesting features that can attract them to read the information about the herbs. The scope of this study covers the range of the target user and also the content of the application. The main target user is the community in UTHM which consist of students and staffs. This Herbs Augmented Reality Applications concentrated on the info of the herbs plant. This application will also be developed in English language. There will be 5 types of herbs which will be displayed. The herbs are turmeric, tongkat ali, asam gelugor, cengkih, and mas cotek. The platform for this application is mobile based platform. The modeling in this application will be in 3D which can capture their mind to be more attracted in using this application.